Rempang di Persimpangan Jalan: Ambisi Pembangunan dan Ketimpangan Sosial di Wilayah Perbatasan - Casiavera Casiavera; Herry Wahyudi; Rizky Octa Putri Charin; Ardi Putra; Khairi Rahmi (Universitas Pendidikan Ganesha, 2026)
This article examines the social, economic, and ecological conflicts stemming from the development of Rempang Eco City, a National Strategic Project (PSN) in the Riau Islands. The research utilizes a descriptive qualitative approach, incorporating in-depth interviews with four participants. There are 33 questions in the interview, but only 22 of them are important, this is related to the saturation data found in the interview questions. It took a month to obtain the information. The results indicate that traditional ways of making a living are disappearing, people are moving and breaking up communities, the economy is weak, and women have trouble getting to natural resources because of things like coastal degradation, land and green grabbing, and limited access to natural resources. The government and investors focus on the long-term economic benefits, but local communities have to deal with social and environmental problems that are worse than the money they get. This article adds to the field of political ecology by talking about the developmental paradox: instead of promoting inclusive prosperity, the project makes social inequality worse, hurts environmental sustainability, and puts the cultural identity of indigenous borderland communities at risk.